The Illocutionary Meanings Of Questions In Life Is Beautiful Movie - Widiawanti, Wiwit; , Agus Wijayanto, Ph.D (2017)
The research aimed to identify the types of questions form and analyze the illocutionary meaning of question in Life is Beautiful Movie. The researcher uses descriptive qualitative method as research method. The data source of this research is Life is Beautiful movie manuscript. Data are analyzed by using Searle's (1979) theory of illocutionary act to analyze the illocutionary meanings, Hymes' theory (1974) to provide the situational context of the conversation in Life is Beautiful movie. The result of the study shows that 250 data containing of types of questions employed by the characters in Life is Beautiful movie. They are WH-Question with the percentage of 68.4%, Yes-No question with 27.6%, and Tag-Question with only 4%. After identifying the types of question form, the researcher analyzes the illocutionary meaning of question in Life is Beautiful Movie. The researcher also found 4 classification of illocutionary act based on the context of conversation in this Movie, there are representatives, expressive, directives, commissives, and declaratives is not found in this movie. Keywords: types of question form, illocutionary meaning, and context